1999
DOI: 10.1136/ard.58.6.350
|View full text |Cite
|
Sign up to set email alerts
|

Increased vulnerability of postarthritic cartilage to a second arthritic insult: accelerated MMP activity in a flare up of arthritis

Abstract: were found to be present in the cartilage before induction of a flare up. (Ann Rheum Dis 1999;58:350-356)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…The C-terminal neoepitope DIPEN 341 ( Fig. 1c) has been immunolocalized in human articular and intervertebral disc cartilage (9,10) and in experimentally induced arthritis models in mice (13,14,(23)(24)(25)(26), providing evidence that MMPs directly degrade aggrecan in vivo.…”
mentioning
confidence: 98%
“…The C-terminal neoepitope DIPEN 341 ( Fig. 1c) has been immunolocalized in human articular and intervertebral disc cartilage (9,10) and in experimentally induced arthritis models in mice (13,14,(23)(24)(25)(26), providing evidence that MMPs directly degrade aggrecan in vivo.…”
mentioning
confidence: 98%
“…Proteolysis in the IGD releases the entire chondroitin sulfate and keratan sulfate-rich regions essential for the biomechanical properties of aggrecan, and is therefore thought to be the most detrimental for cartilage function. In pathology, proteolysis is driven mainly by aggrecanases, but there may also be some involvement of matrix metalloproteinases (MMPs) in late stage disease (1)(2)(3). "Aggrecanase" was first identified as a novel activity that cleaved the aggrecan core protein at the E 373 2 374 A bond in the IGD (4 -6) and at four specific sites in the CS-2 domain (5,6).…”
mentioning
confidence: 99%
“…Our previous in vitro studies suggested that MMPs are involved in the baseline turnover of aggrecan, whereas aggrecanases drive accelerated turnover. Other studies in mouse models of arthritis suggest that aggrecanases are involved in initiating early aggrecan loss and cartilage damage but that severe, late-stage disease may be MMP driven (74)(75)(76). The major aggrecanase in articular cartilage appears to be ADAMTS-5 (64).…”
mentioning
confidence: 99%